Optimization of Silkworm Sericin Extraction Attacus atlas and Samia cynthia ricini Using Response Surface Methodology - Yuni Cahya Endrawati; Dedy Duryadi Solihin; Ani Suryani Suryani; Noviyan Darmawan Darmawan; Irma Herawati Suparto; Bella Fitri Rahmantika (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2023)
Silk fiber is an organic waste that can pollute the environment due to its solubility in processing wastewater. The extraction from wastewater was carried out to reduce environmental pollution and produce natural bioactive. Therefore, this research aims to produce an extraction method that maximizes the protein yield of Attacus atlas (A. atlas) and Samia cynthia ricini (S. ricini) sericin and analyze the characteristics. The method consists of two stages, the optimization of sericin protein extraction with Response Surface Methodology (RSM) and its characterization. The optimization resulted in the optimum extraction of A. atlas and S. ricini sericin at a concentration of 0.08 and 0.03 N NaOH, temperature of 130.52 °C and 113.20 °C, time of 71.71 and 33.78 minutes with a yield of 17.39±1.24% and 20.24±2.30%. The sericin protein had a molecular weight of 8.99 and 7.08 kDa in A. atlas and S. ricini. The extraction produces glycine, alanine, and tyrosin for A. atlas and glutamic acid, glycine, and alanine for S. ricini. Therefore, the sericin extraction formulation did not change the secondary structure protein, as evidenced by the FTIR results.